Blame Games and Climate Change: Accountability, Multi-Level Governance and Carbon Management. (February 2015) - Bache, Ian; Bartle, Ian; Flinders, Matthew; Marsden, Greg
Research Highlights and Abstract This article provides the first detailed and evidence-based account of the coalition government's approach to transport-related carbon management. It exposes the existence of a 'governance vacuum' between the statutory target and a very weak devolved implementation system (i.e. 'fuzzy governance' and 'fuzzy accountability'). Research in four major city regions reveals a systemic switch from an emphasis on carbon management and reduction towards economic growth and job creation. Officials within the policy design and delivery chain emphasise the manner in which the demands of democratic politics tend to frustrate meaningful policy change. A general demand by actors at the local level not for the discretions delivered by localism but for a more robust and centrally managed—even statutory—governance framework. The Climate Change Act 2008 received global acclaim for embedding an ambitious set of targets for the reduction of carbon emissions in legislation. This article explores the policies and institutional frameworks in place to deliver transport-related carbon reductions as part of the subsequent Carbon Plan. A detailed methodology involving institutional mapping, interviews and focus groups combined with a theoretical approach that combines the theory of multi-level governance with the literature on 'blame avoidance' serves to reveal a complex system of 'fuzzy governance' and 'fuzzy accountability'. Put simply, it reveals there are no practical sub-national implementation levers for achieving the statutory targets. Apart from symbolic or rhetorical commitments, the emphasis of policy-makers at all levels in the delivery chain has switched from carbon management and reduction to economic growth and job creation. This raises fresh research questions about the pathologies of democratic competition and future responses to the climate change challenge.